Interpretation and Indexicality (Aporia, 2020)
The paper objects to the treatment of descriptive uses of indexicals proposed by Nunberg (1993). It is shown that the arguments Nunberg presents are ineffective against a pragmatic account of these uses such as that put forth by Recanati (1993). The conclusion is that there are good reasons to believe that the deferred interpretation in question are generated by non-semantic processes involving extralinguistic factors such as the speaker's communicative intentions.